2020
DOI: 10.1007/s42461-020-00306-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective Extraction of Zinc from Zinc Ferrite

Abstract: The presence of iron in sphalerite induces the formation of zinc ferrite (ZF) during roasting. Zinc refinery residues (ZRR) and electric arc furnace dust (EAFD) contain a significant amount of zinc ferrite and are difficult to treat. According to the literature, up to 71% ZF has been found to be present in ZRR. The dissolution of zinc ferrite is inefficient even in aqua regia. The Waelz process is an existing process to recover zinc from electric arc furnace dust by reduction using carbon monoxide followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Dutra [23] and Orhan et al [24] obtained 74% and 85% Zn recovery, respectively, by conventional alkaline leaching experiments and suggested that the insolubility of ZnFe 2 O 4 in the dust was the main reason for the low leaching rate. Due to the low aqueous solubility of zinc ferrite, most of the hydrometallurgical processes are not economically feasible for the extraction of zinc or iron as zinc residues typically contain only 15-20% of zinc and iron [25].…”
Section: Introductionmentioning
confidence: 99%
“…Dutra [23] and Orhan et al [24] obtained 74% and 85% Zn recovery, respectively, by conventional alkaline leaching experiments and suggested that the insolubility of ZnFe 2 O 4 in the dust was the main reason for the low leaching rate. Due to the low aqueous solubility of zinc ferrite, most of the hydrometallurgical processes are not economically feasible for the extraction of zinc or iron as zinc residues typically contain only 15-20% of zinc and iron [25].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have studied other leaching methods for the processing of zinc ferrite residue by sulfuric acid [ 11 , 12 , 13 ], di-2-ethylhexyl phosphoric acid [ 14 ], sodium hydroxide [ 15 , 16 ], chloride solutions [ 17 , 18 , 19 ], and even by ionic liquids [ 20 ] and deep-eutectic solvents [ 21 ]. The methods using pyrometallurgical processing of such materials by reduction roasting [ 22 , 23 , 24 , 25 ], sulfiding roasting [ 26 , 27 ], roasting with the addition of sodium compounds [ 28 , 29 , 30 , 31 ], chloride volatilization process [ 32 ] were also reported. However, these methods are still hardly applicable in the industrial practice.…”
Section: Introductionmentioning
confidence: 99%
“…Since zinc and iron tend to be companions in common use and zinc-bearing minerals, co-treatment of massive zinc and iron containing materials at the furnace brings about zinc ferrite, which is a stable phase causing trouble in recycling zinc [2,3]. Many solid wastes such as zincbearing flue dust and zinc leaching residue are reported to contain considerable amounts of zinc ferrite [4]. To realize resource recycle, carbothermal reduction method has been long used, followed by obvious drawbacks including coal consumption, slag stockpile and loss of non-volatile metals [5].…”
mentioning
confidence: 99%